(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Prognosis of environmental quality in Baltic states related with the closure of Ignalina Nuclear Power Plant according to two electricity production scenarios was made. (Scenario 1 - closure date of Block 1 is 2005, closure date of Block 2 is 2011; Scenario 2 - closure date of Block 1 is 2005, exploitation of Block 2 will be extended at least until 2020.) We can see that in accordance with both scenarios CO2 an SO2 emission will increase every year. Although the influence of the largest air pollution sources such as Estonian/Baltic PP, Lithuanian PP Riga CHP and others remains very significant to the situation in Baltic States, new power plants will forward the rise of total emission.